Upaya pemberdayaan pasien dan keluarga dalam meningkatkan kepatuhan restriksi cairan Pasien Hemodialisis di RS dr. Soekardjo Kota Tasikmalaya - Ida Rosdiana; Yanti Cahyati; Yudi Triguna (Yayasan Inspirasi El Burhani, 2023)
Introduction: Weight gain in the time between two dialysis sessions, also known as interdialysis weight gain (IDWG), is one of the most frequent issues that patients with chronic renal disease who get hemodialysis experience. A too-high IDWG result might exacerbate the patient's symptoms by causing hypotension, cramping in the muscles, hypertension, dyspnea, nausea, and vomiting, among other things. Objective: This community service activity aims to increase patient and family independence by increasing fluid restrictions compliance. The goal is for families and patients to be equipped with the information and abilities necessary to avoid adding too much IDWG. The method used is conducting training for patients and families and creating educational media. 38 people, including accompanying family members and HD patients, attended the training. Pre-test questions are distributed at the start of training, and post-test questions are distributed after the session to assess the activities. The training consists of providing material and training on maintaining fluid balance, overcoming thirst, and calculating HD patients' fluid needs. Result: The training results obtained data on patient and family knowledge about the importance of fluid management in HD patients. The facilities and infrastructure used include leaflets about fluid management for HD patients. This community service project improves patient and family knowledge and skills, educational media, and community dissemination of the activities' outcomes. Conclusion: To increase hemodialysis patients' compliance with fluid restrictions, steps must be taken to empower patients and families.